Essential sports nutrition a guide to optimal performance for every active person - Sumbal, Marni (Rockbridge Press, 2018)
Sports nutrition is a vital element for reaching peak physical performance. To maximize workouts and athletic ability, Essential Sports Nutrition offers the most up-to-date nutritional guidance along with delicious recipes to make eating right for an active lifestyle, easy. Complete with 24 recipes for before, after, and during exercise, Essential Sports Nutrition is a user-friendly reference on fueling to meet your fullest potential.